THE CHANGES OF THE AİR TEMPERATURE CHARACTERİSTİCS İN THE AZERBAİJAN TERRİTORY DURING GLOBAL CLİMATE CHANGES PERIOD - HUSEYNOV, Jamal; TAGIYEV, Allahverdi (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Background. Air temperature observation data covering the years 1981–2022 of about 70 hydrometeorological stations operating in the territory of the Republic of Azerbaijan were used in the study. In order to determine the influence of climate changes on the air temperature regime, the results of 1981–2010 were compared with the corresponding results of 2011–2022.Methods. In the study, the trend of monthly, seasonal and multiannual changes in air temperature was considered using mathematical, statistical and cartographic methods.Results. Studies show that the air temperature has increased by 0.90C at the country level. The positive anomaly has been reached to 1.3° C at the belt with an altitude of 2001–2500 m. The main high indicators were noted in highland regions. The temperature anomaly is in the range of 1.5–1.7° C, mostly in May and June months. Long-term temperature dynamics show that in 2001–2010 the temperature increase (0.057° C / 1 year) is observed. It was the warmest time during 1961–2022 comparing with previous decade.The results of the study can be used in the protection against climate changes, mitigation and studying the modern temperature regime. In addition, solar radiation can be used as an alternative energy source in flat areas where high air temperature indicators are observed. The results will be announced at the conference on climate change COP 29 (Conferences of the Parties), which will be held in Baku on November 11–22, 2024.Conclusions. The influence of climate changes in the air temperature regime in the territory of Azerbaijan will lead to the disruption of the traditional climate regime, the disappearance of the green landscape and expansion of semi-desert and arid landscape in the front mountainous areas, the increase of possible evaporation and the increasing of environmental crises such as drought at the 1000 m elevations. An increase in the radiation balance in Nakhchivan province may worsen the continentality of the climate type here. The increase in temperature in the Kura depression province will create conditions for the expansion of the semi-desert-arid climate in the piedmonts of the Greater Caucasus Mountains.
Keywords: mathematical; statistical and cartographic methods; temperature indicators; greenhouse effect; flat areas; alternative energy source; climate norm; altitude zone; ArcGIS